Geographic Information System -Based Map for Best Suitable Place for Cultivating Permanent Trees in South-Lebanon (Global Journal of Human-Social Science, 2018)
To reduce the human influence on nature resources and to identify an appropriate land use, it is essential to carry out scientific land evaluation. Such kind of analysis allows identifying the main factors for agricultural production and enables decision makers to develop crop managements able to increase the land productivity. Land capability is the ability of land to sustain a type of land use permanently. The key is to match the type and intensity of land use with its natural capability. Therefore; in order to benefit from these areas and invest them to obtain good agricultural production, they must be organized and managed in full. Lebanon suffers from the unorganized agricultural use, we take south Lebanon as study area, due to it is the most fertile ground and have a variety in crops. The study aims to identify and locate the most suitable area to cultivate thirteen type of permanent trees which are: apples, avocadoes, stone fruits in coastal regions and stone fruits in mountain regions, bananas, citrus, loquats, figs, pistachios, mangoes, olives, pomegranates and grapes. Several geographical factors are taken as criterion for selection of the best location to cultivate. Soil, rainfall, PH, temperature and elevation, are main inputs to create the final map. Input data of each factor is managed, visualized and analyzed using Geographic Information System (GIS). Managements GIS tools are implemented to produce input maps capable of identifying suitable areas related to each index.
Keywords: agricultural pr oduction; crop managements; geographical factors; geographic information system (GIS); land capability